Evaluating soil loss from ephemeral gullies with photogrammetry - Weerasekara, Chinthaka Bandara (Kansas State University, 2019)
Sedimentation is a significant threat to water reservoirs and streams in Kansas, the Central Great Plains in the United States, and worldwide. Soil erosion in agricultural fields is one of the primary environmental concerns and a major contributor to sedimentation. Ephemeral gullies (EG) are localized areas of soil erosion that form from concentrated water flow in upland areas. Soil erosion from EGs in agricultural fields contributes a substantial fraction of annual upland sediment and does so disproportionally (relative to other sources) during higher-flow events. Limited evidence exists of documented EG development during a crop growing season, thus there is a need for field experiments with frequent EG surveying. Close-range photogrammetry is a method of creating digital elevation maps from a set of photographs that can be used for EG erosion assessment. Main objectives of this study were to develop an EG monitoring method based on photogrammetry technique, apply it to ephemeral channels in a no-till field in northeast Kansas, and evaluate the factors related to EG development. A close-range photogrammetry method was first designed and conducted in the lab experiment in order to evaluate the produced model accuracy, ground control point density, and their spatial distribution. For most accurate results, it was determined that optimal ground control point density was 3 to 4 points per 1 m², 60% or more of photograph image overlap, and a camera tilting angle between 0⁰ and 30⁰. Twelve repetitive photogrammetry surveys were conducted for field surveying of three EGs over a two-year period from 2016 to 2018. The produced 3-D digital surface models were analyzed to identify specific EG topographic features, evaluate the changes in EG surface area, width, depth, rates of growth, and seasonal soil loss estimates. Unique patterns of soil erosion during crop growing season and sediment accumulation within the gullies were observed for all EGs.
Keywords: Soil erosion; Ephemeral gully; Photogrammetry; Evaluate soil loss; Ephemeral gully monitoring